2015
DOI: 10.1159/000438739
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of Thalassemia among Pregnant Laotian Women

Abstract: Background and Aims: A pilot screening program for thalassemia was initiated in the Lao People's Democratic Republic. This study aimed to describe the genotype diversity and hematologic features of thalassemia among the participating pregnant women. Methods: Blood samples of 411 pregnant Laotian women were collected. Hemoglobin (Hb) profiles were determined using a capillary zone electrophoresis system. Mutations of α- and β-globin genes were investigated using a polymerase chain reaction and related technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
(20 reference statements)
4
15
0
Order By: Relevance
“…A marked reduction in MCV and MCH with mild anemia was observed in all forms of Hb E homozygotes. These hematologic changes were consistent with our previous studies Fucharoen et al 2004Fucharoen et al , 2006Savongsy et al 2008;Wongprachum et al 2016). Based on hematological parameters reported here, anemia seems not to be a major health burden in this minority group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A marked reduction in MCV and MCH with mild anemia was observed in all forms of Hb E homozygotes. These hematologic changes were consistent with our previous studies Fucharoen et al 2004Fucharoen et al , 2006Savongsy et al 2008;Wongprachum et al 2016). Based on hematological parameters reported here, anemia seems not to be a major health burden in this minority group.…”
Section: Discussionsupporting
confidence: 93%
“…However, such cases appear to be rare. Based on our data collected independently from several communities Sanchaisuriya et al 2006;Savongsy et al 2008;Panomai et al 2010;Tritipsombut et al 2012;Wongprachum et al 2016), only 0.09% (2/2329) of individuals with normal MCV had elevated Hb A 2 . Nonetheless, our study provides evidence supporting the remarkably high Hb CS in ethnic minority groups in Central Vietnam.…”
Section: Discussionmentioning
confidence: 94%
“…Confirming previous data, our results demonstrate that thalassemias and hemoglobinopathies are highly prevalent and heterogeneous in the Lao population, with over 20 different genotypes being identified. The genotype and pattern of thalassemia genes detected in this study are similar to those reported in pregnant women . The results of this work indicate that thalassemias and hemoglobinopathies are a serious public health problem in the Lao PDR.…”
Section: Discussionsupporting
confidence: 84%
“…The interaction of these three forms of thalassemia may lead to a high prevalence of severe thalassemia syndrome, including the homozygous α 0 , homozygous β 0 , and β‐thalassemia/HbE types, which may affect public health in this community. Based on gene frequency analysis, we and previous authors found that the frequency of ‐‐ SEA /αα is more prevalent than that of the ‐α 3.7 /αα deletion in the Lao population. This α‐thalassemia frequency differs from those reported in neighboring South East Asian countries, including Vietnam, Thailand, and Cambodia, which show a higher frequency of the –α 3.7 deletion.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation